(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
This article explores the significance of the linguo-cultural component in foreign language teaching. It highlights how integrating cultural aspects with linguistic instruction not only enhances learners’ communicative competence, but also deepens their intercultural understanding. The paper examines various approaches and effective strategies for combining language skills with cultural content, emphasizing the necessity of authentic materials and real-life context in the classroom. The importance of fostering cultural awareness and sensitivity among language learners is also discussed, considering the globalization and internationalization of education.